FOXN1 mutation abrogates prenatal T-cell development in humans. Issue 6 (19th April 2011) - Vigliano, I; Gorrese, M; Fusco, A; Vitiello, L; Amorosi, S; Panico, L; Ursini, M V; Calcagno, G; Racioppi, L; Del Vecchio, L; Pignata, C
Abstract : Background: The transcription factor FOXN1 is implicated in the differentiation of thymic and skin epithelial cells, and alterations in it are responsible for the Nude/SCID phenotype. During a genetic counselling programme offered to couples at risk in a community where a high frequency of mutated FOXN1 had been documented, the identification of a human FOXN1 −/− fetus gave the unique opportunity to study T cell development in utero. Results: Total blockage of CD4 + T cell maturation and severe impairment of CD8 + cells were documented. Evaluation of the variable-domain β-chain (Vβ) families' usage among T lymphocytes revealed that the generation of T cell receptor (TCR) diversity occurred to some extent in the FOXN1 −/− fetus, although it was impaired compared with the control. A few non-functional CD8 + cells, mostly bearing TCRγδ in the absence of CD3, were found. Discussion: FOXN1 is crucial for in utero T cell development in humans. The identification of a limited number of CD8 + cells suggests an extrathymic origin for these cells, implying FOXN1-independent lymphopoiesis.